Perspevctives and challenges of digital development in Ukraine - Полозова, Т. В.; Шейко, І. А. (ХНУРЕ, 2021)
Digitalization becomes the frontier of innovations in industry and social services. All countries at global level provided actions to improve their digital development. The global economy is rapidly becoming digital. Information and Communications Technology (ICT) is no longer a specific sector but the foundation of all modern innovative economic systems. The Internet and digital technologies are transforming production process worldwide.
DOI: 10.30837/978-966-659-334-7
Keywords: digitalization; digital; innovation